VNAR development through antigen immunization of Japanese topeshark (Hemitriakis japanica) - Takeda, Hiroyuki; Ozawa, Tatsuhiko; Zenke, Hiroki; Ohnuki, Yoh; Umeda, Yuri; Zhou, Wei; Tomoda, Honoka; Takechi, Akihiko; Narita, Kimiyoshi; Shimizu, Takaaki; Miyakawa, Takuya; Ito, Yuji; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The VNAR (Variable New Antigen Receptor) is the smallest single-domain antibody derived from the variable domain of IgNAR of cartilaginous fishes. Despite its biomedical and diagnostic potential, research on VNAR has been limited due to the difficulties in obtaining and maintaining immune animals and the lack of research tools. In this study, we investigated the Japanese topeshark as a promising immune animal for the development of VNAR. This shark is an underutilized fishery resource readily available in East Asia coastal waters and can be safely handled without sharp teeth or venomous stingers. The administration of Venus fluorescent protein to Japanese topesharks markedly increased antigen-specific IgM and IgNAR antibodies in the blood. Both the phage-display library and the yeast-display library were constructed using RNA from immunized shark splenocytes. Each library was enriched by biopanning, and multiple antigen-specific VNARs were acquired. The obtained antibodies had affinities of 1 × 10−8 M order and showed high plasticity, retaining their binding activity even after high-temperature or reducing-agent treatment. The dissociation rate of a low-affinity VNAR was significantly improved via dimerization. These results demonstrate the potential utility of the Japanese topeshark for the development of VNAR. Furthermore, we conducted deep sequencing analysis to reveal the quantitative changes in the CDR3-coding sequences, revealing distinct enrichment bias between libraries. VNARs that were primarily enriched in the phage display had CDR3 coding sequences with fewer E. coli rare codons, suggesting translation machinery on the selection and enrichment process during biopanning.